Health care utilization in young adults with childhood physical disabilities: a nationally representative prospective cohort study - Kirkpatrick B. Fergus; Alan Zambeli-Ljepović; Lindsay A. Hampson; Hillary L. Copp; Jason M. Nagata (BMC, 2022)
Abstract Background Young people with physical disabilities face barriers to accessing health care; however, few studies have followed adolescents with physical disabilities longitudinally through the transition of care into adulthood. The objective of this study was to investigate differences in health care utilization between adolescents with physical disabilities and those without during the transition period from adolescent to adult care. Methods We utilized the National Longitudinal Study of Adolescent to Adult Health, a prospective cohort study following adolescents ages 11-18 at baseline (1994-1995) through adulthood. Baseline physical disability status was defined as difficulty using limbs, using assistive devices or braces, or having an artificial limb; controls met none of these criteria. Health care utilization outcomes were measured seven years after baseline (ages 18-26). These included yearly physical check-ups, unmet health care needs, and utilization of last-resort medical care, such as emergency departments, inpatient hospital wards, and inpatient mental health facilities. Multiple logistic regression models were used to predict health care utilization, controlling for age, sex, race/ethnicity, insurance status, and history of depression. Results Thirteen thousand four hundred thirty-six participants met inclusion criteria, including 4.2% with a physical disability and 95.8% without. Half (50%) of the sample were women, and the average age at baseline was 15.9 years (SE = 0.12). In logistic regression models, those with a disability had higher odds of unmet health care needs in the past year (Odds Ratio (OR) 1.41 95% CI 1.07-1.87), two or more emergency department visits in the past five years (OR 1.34 95% CI 1.06-1.70), and any hospitalizations in the past five years (OR 1.36 95% CI 1.07-1.72). No statistically significant differences in preventive yearly check-ups or admission to mental health facilities were noted. Conclusions Young adults with physical disabilities are at higher risk of having unmet health care needs and using last-resort health care services compared to their non-disabled peers.